Online 24 hour hardware lab server characterization and optimization - Ng, Chun Hong (2014)
Learning embedded device development requires practicing on the devices in a laboratory. However school laboratories often have limited resources, which limit the students’ exposure. A virtual interactive lab that allows students to practice programming on embedded devices is a cost-effective solution. The project aims to develop a web-based virtual laboratory, where users can remotely upload programs into microcontroller or bit-stream into FPGA devices and see the result of their work through a live video feed. The primary objective is to provide a laboratory that is enough for undergraduate students to upload a basic program into a microcontroller and watch the result. The Raspberry Pi computer was used to give the virtual lab interactivity. The Raspberry Pi was configured into a server and integrated into the virtual laboratory system, which comprised of a web server and a video server. The Raspberry Pi made it possible for users to remotely control the physical controls on the development board, and to control the ambient lighting for the live video feed. By the end of the project, a working virtual lab was built and put into its paces during the NTU School of Computer Engineering e-learning week. User feedbacks were solicited to gauge the usefulness of the system and identify aspects of the system that require more work. Future work can be done to make a wider range of devices available to users and improve the overall effectiveness of the virtual lab.